Sistemas Dinámicos No Lineales a Partir de Series de Tiempo para el Análisis y Control de Pilas de Combustible - Cruz Cardozo, José Laureano (Universidad Antonio Nariño, 2023)
This work presents a procedure for constructing models of nonlinear dynamic systems that exhibit deterministic chaos behaviors based on time series data. The procedure involves extracting information from the time series to reconstruct the dynamic system in phase space, using second-order equations and three variables. We implemented this procedure in Python as a software and tested it on the well-known Lorenz system, extensively studied in chaos theory.